2021
DOI: 10.3390/genes12060911
|View full text |Cite
|
Sign up to set email alerts
|

A Deep-Learning Sequence-Based Method to Predict Protein Stability Changes Upon Genetic Variations

Abstract: Several studies have linked disruptions of protein stability and its normal functions to disease. Therefore, during the last few decades, many tools have been developed to predict the free energy changes upon protein residue variations. Most of these methods require both sequence and structure information to obtain reliable predictions. However, the lower number of protein structures available with respect to their sequences, due to experimental issues, drastically limits the application of these tools. In add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 39 publications
0
40
0
Order By: Relevance
“…ACDC-NN [ 31 ] and its sequence-based version ACDC-NN-Seq [ 32 ] (stand-alone tool): neural network-based methods whose architectures satisfy the antisymmetry properties by construction. They both take as input the local information from the amino acids in the neighbourhood of the mutation and they both use multiple sequence alignments considering the two amino acids involved in the mutation.…”
Section: Methodsmentioning
confidence: 99%
“…ACDC-NN [ 31 ] and its sequence-based version ACDC-NN-Seq [ 32 ] (stand-alone tool): neural network-based methods whose architectures satisfy the antisymmetry properties by construction. They both take as input the local information from the amino acids in the neighbourhood of the mutation and they both use multiple sequence alignments considering the two amino acids involved in the mutation.…”
Section: Methodsmentioning
confidence: 99%
“…The benchmarked predictors included sequence-based and structure-based predictors for a fair comparison. Sequence-based predictors included IMutant, iStable, STRUM, EASE-MM, INPS, BoostDDG, iStable2.0_SEQ, SAAFEC-SEQ, DDGun, and ACDC-NN-Seq . On the basis of the current literature, it was concluded that sequence-based predictors might have performance issues, so we also included the structure-based predictors, including SDM, FoldX, mCSM, DUET, MAESTRO, PoPMuSiC, SDM2, DeepDDG, iDeepDDG, PoPMuSiCSym, and DDGun3D for the performance benchmarking.…”
Section: Resultsmentioning
confidence: 99%
“…Sequence-based predictors included IMutant, 45 iStable, 17 STRUM, 46 EASE-MM, 47 INPS, 18 BoostDDG, 20 iStable2.0_SEQ, 48 SAAFEC-SEQ, 21 DDGun, 12 and ACDC-NN-Seq. 19 On the basis of the current literature, it was concluded that sequence-based predictors might have performance issues, 3 so we also included the structure-based predictors, including SDM, 9 FoldX, 8 mCSM, 13 DUET, 15 MAESTRO, 16 PoPMuSiC, 49 SDM2, 10 DeepDDG, 14 iDeepDDG, 14 PoPMuSiCSym, 11 and DDGun3D 12 for the performance benchmarking. Here, we performed multiple cross-validation tests using the S2647 direct mutations, S2647 inverse mutations, and S5294 (S2647 direct mutations + S2647 inverse mutations) training data sets.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations